Atherogenesis in the carotid artery with and without interrupted blood flow of two hyperlipidemic mouse strains - Zhao, Jian (J Vasc Res, 2019)
PURPOSE: Atherosclerosis in the carotid arteries is one common cause of ischemic stroke. We examined atherogenesis in the left carotid artery with and without interrupted blood flow of C57BL/6 (B6) and C3H Apoe-deficient (Apoe(−/−)) mouse strains. METHODS: Blood flow was interrupted by ligating the common carotid artery near its bifurcation in one group of mice and other group was not interrupted. RESULTS: Without interference with blood flow, C3H Apoe(−/−) mice developed no atherosclerosis in the carotid artery while B6 Apoe(−/−) mice formed advanced atherosclerotic lesions (98,019 ± 10,594 μm(2)/section) after 12 weeks of Western diet. When blood flow was interrupted by ligating the common carotid artery near its bifurcation, C3H Apoe(−/−) mice showed fatty streak lesions 2 weeks after ligation and by 4 weeks fibrous lesions formed though smaller than B6 Apoe(−/−) mice. Neutrophil adhesion to endothelium and infiltration in lesions was observed in ligated arteries of both strains. Treatment of B6 Apoe(−/−) mice with antibody against neutrophils had little effect on lesion size. CONCLUSIONS: These findings demonstrate the dramatic influences of genetic backgrounds and blood flow on atherogenesis in the carotid artery of hyperlipidemic mice.